Client-consultant relationship in building development projects in Singapore - Lee, Meng Hoon. (2008)
The purposes of this study are I) to understand client and consultant relationship in a building construction project ii) to identify possible causes of problems/conflicts in such a relationship iii) to make recommendations to reduce conflicts and ways to strengthen good relationship